An Agricultural Water Use Package for MODFLOW and GSFLOW. (March 2020) - Niswonger, Richard G.
Abstract: The Agricultural Water Use (AG) Package was developed for simulating demand-driven and supply-constrained agricultural water use in MODFLOW and GSFLOW models. The AG Package uses pre-existing hydrologic simulation provided by MODFLOW and GSFLOW. Three options are available for simulating water use for agriculture: (1) user-specified demands, (2) demands determined by a user-specified irrigation trigger value that is compared to the ratio of the simulated actual to potential evapotranspiration (ET), and (3) demands determined by minimizing the difference between potential and actual ET. The latter two approaches use energy and soil-water balance to determine crop-water demands. Irrigation withdrawals are diverted into canals and routed to fields using the MODFLOW SFR Package, or irrigation water is provided/supplemented by groundwater. Combined with MODFLOW or GSFLOW, the AG Package can simulate dynamic water use by agriculture in developed basins while providing flexibility to represent a range of irrigation practices. Highlights: New package for MODFLOW and GSFLOW to represent agricultural water use. Package can estimate irrigation demands using field-scale dynamic soil-water balance for large river basins. Package can convert estimates of actual ET, such as from Landsat, to irrigation withdrawals for large river basins.